Insider Intervention Model in the Sabotage Attack Scenario of a Nuclear Reactor Facility - Andiwijayakusuma, Dinan; Asmoro, Teguh; Mardhi, Alim; Setiadipura, Topan (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2024)
The Physical Protection System (PPS) at nuclear facilities aims to prevent intrusions into nuclear facilities that cause sabotage attacks or illegal theft of nuclear material. The outsider, the insider or a collaboration of both can carry out this intrusive action. In this study, we modelled the insider collaborating with the outsider to carry out nuclear facility attacks using sabotage attack scenarios. The modelling takes the form of insider intervention on two parameters protection elements:the time delay () and the probability of detection (). Insider intervention in delay protection elements might have fatal consequences and drastically reduce the effectiveness of PPS performance. Therefore, PPS designers need to pay more attention to the delay element to anticipate the negative impact of insider intervention on the effectiveness of the PPS.